The Effects of private exercises in the back speed to the control area (T) and the low-lying straight offensive strike in squash within ages (17-19) years - Jihad, Ali; Saab, Mohammed (Journal of Physical Education, 2015)
The Research contained the introduction, research importance and the problem which summarized that there is a clear frequency in the performance of low-lying strikes straight front and rear and the lack of use in games and the slow in speed to the control area (T) in the research sample. The aim of the research is to identify the effect of exercise for the speed back to the control area (T) and low-lying straight offensive strike among the youth team squash players within ages 17-19 years, The research imposition is there are significant differences were statistically significant differences between pre and post tests in speed Back to the control area (T) and low-lying straight offensive strike to the youth team squash players aged (17-19 years) and in the post test. The researcher select a sample by the intentional method, which included youth team squash players aged (17-19), who numbered (8) players, were excluded (2) players to do exploratory experiences on them, so the samples number become (6) players during the stages of the application Exercise who represent the proportion (75%) of the original community, it has been identified research tests by Arab and foreign sources, and after completing the exploratory and testing tribal experience, the private exercises has been applied on the samples according to established training modules for the statement impact in the developing the level of the sample and then was conducted posteriori tests and then processing the results through the program (spss), then view and analyze and discuss the results of tests of physical and skill tests and that the results showed that there are significant differences in favor of a posteriori tests for the research sample